PROFITABILITAS BANK PERKREDITAN RAKYAT DI KOTA PADANG DI TINJAU DARI RASIO LIKUIDITAS - Afriyeni, Afriyeni (LLDIKTI Wilayah X, 2017)
The purpose of this study is to examine the effect of liquidity as measured by LDR (Loan to Deposit Ratio) and Loan to Asset Ratio on the profitability (Return on Asset) of Rural Bank (BPR) in Padang City. The data used are secondary data obtained by documentation method taken from publication reports of Bank Indonesia and Rural Banks in Padang City during the period of 2010 - 2015 quarter. The population used in this study are all existing BPR in Padang city and sample selection Based on purposive sampling with the number of 93 observations. Data analysis was done by using multiple linear regression. The results showed that the liquidity measured by the ratio of LDR and LAR did not significantly affect the profitability (ROA) of BPR in Padang City.